Prevalence of sarcopenia and associated factors in patients in hemodialysis - Nunes, Camila Ferreira (2021)
Objective: To assess the prevalence of sarcopenia and associated factors in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD). Methods: This cross-sectional study evaluated patients with CKD undergoing HD from January to October 2016 in two dialysis centers located in Recife, Pernambuco. For the diagnosis of sarcopenia, the criteria proposed by the 2019 European Consensus on Sarcopenia, which advocates low muscle strength as the main criterion, were considered. Demographic, clinical, anthropometric, and behavioral covariates were evaluated. Results: 108 patients were included, with a mean age of 51.4 ± 17.0 years and homogeneous distribution between the sexes.Sarcopenia was present in 38.9% of the population, of which 69% had severe sarcopenia. A higher prevalence of sarcopenia was observed among men (60% vs. 17%; p < 0.001), in those without a partner (48.1% vs. 30.4%; p < 0.045), in smokers (50% vs. 30%; p < 0.034), with low weight (underweight 73.3%, eutrophic 33.9%, overweight 32.4%; p = 0.001) and those with normal albumin levels (47.5% vs. 28.6%; p = 0.045). Conclusion: Approximately one in three nephropathic patients on hemodialysis presented sarcopenia and, among these, most had the severe form of this condition.Uremic sarcopenia was more prevalent in males, in individuals without partners, underweight, in smokers, and among those with normal albumin levels.